Effect of Alkyl Chain Length on Adsorption Behavior and Corrosion Inhibition of Imidazoline Inhibitors - Hojat Jafari; Farhhad Mohsenifar; Koray Sayin (Iranian journal of chemistry & chemical engineering, 2018)
Inhibition performances of imidazoline derivatives with different alkyl chain length for carbon steel in H2S acid solutions has been studied by polarization curves, AC impedance measurements, current transient, Atomic Force Microscopy (AFM) and Density Functional Theory (DFT) techniques. Results showed that the inhibition occurs through adsorption of the inhibitors molecules on the metal surface. The inhibition efficiency was found to increase with increasing inhibitor’s concentration. Polarization data indicated that these compounds act as mixed-type inhibitors. Computational studies of investigated inhibitors were performed by using Hartree–Fock (HF) and M062X methods which are ab-initio and DFT methods with 6-31G basis set in the gas phase and water. Calculated results indicate that the inferred inhibition efficiency increases with the increasing alkyl chain length, which is well in accordance with reported experimental results.